2013
DOI: 10.1038/bjc.2013.325
|View full text |Cite
|
Sign up to set email alerts
|

Inducing apoptosis of cancer cells using small-molecule plant compounds that bind to GRP78

Abstract: Background:Glucose regulated protein 78 (GRP78) functions as a sensor of endoplasmic reticulum (ER) stress. The aim of this study was to test the hypothesis that molecules that bind to GRP78 induce the unfolded protein response (UPR) and enhance cell death in combination with ER stress inducers.Methods:Differential scanning calorimetry (DSC), measurement of cell death by flow cytometry and the induction of ER stress markers using western blotting.Results:Epigallocatechin gallate (EGCG), a flavonoid component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…Recent studies have concluded that EGCG has binding affinity to the nucleotide binding (ATPase) domain of GRP78 and once bound, EGCG inhibits GRP78 association with ATP by competitive inhibition [15,16]. Thus, it inhibits the ATPase activity of GRP78.…”
Section: Inhibitors Against Grp78mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have concluded that EGCG has binding affinity to the nucleotide binding (ATPase) domain of GRP78 and once bound, EGCG inhibits GRP78 association with ATP by competitive inhibition [15,16]. Thus, it inhibits the ATPase activity of GRP78.…”
Section: Inhibitors Against Grp78mentioning
confidence: 99%
“…EGCG and OSU-03012 binding to GRP78: some mechanistic insights Differential scanning calorimetry experiments indicate that EGCG binds to unfolded form of GRP78 NBD [16]. These authors mention in their paper, BIt is likely that, by analogy with HSP-70 (Liu et al, 2010), an intrinsic mobility of the GRP78 N-terminal domain unfolds it sufficiently to facilitate access of EGCG or HNK under prolonged incubation conditions of a few hours or more^.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…4,5 Surprisingly, p53 mutations are very rare in melanoma, but activity is, however, impaired through direct or indirect inactivation of key elements of this pathway, including through the suppression of APAF-1 expression, 6 loss of PTEN function, 7 dysregulation of Bcl-2 expression, 8 upregulation of the anti-apoptotic protein Mcl-1 together with its altered slice variant expression 9,10 and the ER chaperone GRP78. [11][12][13] Oncogenic mutations, however, in the Ras/Raf pathway are the most well-described genetic mutations associated with melanoma development and progression. 14 Indeed, up to 90% of all melanomas harbour activating NRAS or BRAF mutations, with BRAF V600E representing more than 90% of BRAF mutations, 15,16 the consequence of which is the constitutive activation of RAF-extracellular signal-regulated kinase/ERK signalling promoting melanoma proliferation and resistance to apoptosis.…”
mentioning
confidence: 99%
“…However, the present study did not review the experimental literature concerning patients with osteosarcoma. In addition, numerous studies have demonstrated that GRP78 represents a concordant mechanism of drug resistance in malignant tumors, and could therefore be applied as a predictor for guiding the treatment for patients (11,(20)(21)(22)(23). The present study aimed to investigate the expression of GRP78 in patients with osteosarcoma, and to analyze the expressional differences in tumor tissue and normal tissue, chemotherapy-and non-chemotherapy-treated patients, and metastatic and non-metastatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In view of its importance for the survival of cancer cells, GRP78 could be used as an anticancer drug target. Certain anticancer compounds, such as plant-derived genistein, (-)-Epigallocatechin gallate, honokiol and salicylic acid could be used to inhibit the expression or activity of GRP78 (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%